Outcomes in CME/CPD - Special Collection: How to make the “pyramid” a perpetuum mobile - Griebenow, Reinhard (J Eur CME, 2020)
Continuing medical education (CME) should not be an end in itself, but as expressed in Moore’s pyramid, help to improve both individual patient and ultimately community, health. However, there are numerous barriers to translation of physician competence into improvements in community health. To enhance the effect CME may achieve in improving community health the authors suggest a kick-off/keep-on continuum of medical competence, and integration of aspects of public health at all levels from planning to delivery and outcomes measurement in CME.